2022
DOI: 10.1364/optica.456481
|View full text |Cite
|
Sign up to set email alerts
|

High-order harmonic generation in an x-ray range from laser-induced multivalent ions of noble gas

Abstract: Tabletop coherent x-ray sources extending to multi-keV or higher photon energies have versatile applications, including in 4D imaging and semiconductor detectors. However, these sources can be realized only via high-order harmonic generation (HHG) with an ∼ 10 µ m laser interacting with neutral atoms. As shown in previous work by Popmintchev et al. [Science 350, 1225 (2015)10.1126/science.aac9755SCIEAS0036-8075], multiply ionized plasmas can efficiently pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…Recently, the cut-off photon energy in HHG has been pushed into the kiloelectron volt range, that is, to 5.2 keV (ref. 45 ), and the intracavity HHG was spread into the extreme ultraviolet light range 46 , with an expected spectral width of each harmonic of the order of 0.1 Hz (refs. 47 , 48 ), which would perfectly match the spectral width of the 45 Sc resonance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the cut-off photon energy in HHG has been pushed into the kiloelectron volt range, that is, to 5.2 keV (ref. 45 ), and the intracavity HHG was spread into the extreme ultraviolet light range 46 , with an expected spectral width of each harmonic of the order of 0.1 Hz (refs. 47 , 48 ), which would perfectly match the spectral width of the 45 Sc resonance.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear oscillators are better than atomic oscillators because of their naturally higher quality factors and higher resilience against external perturbations [7][8][9] . One of the most promising cases is an ultra-narrow nuclear resonance transition in 45 Sc between the ground state and the 12.4-keV isomeric state with a long lifetime of 0.47 s (ref. 10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible to breakthrough the limitation of saturation effect by generating IAP/HHG with ions whose ionization threshold is much higher than neutral atoms. It has been shown that the cut-off energy can be extended to above 500 eV with multiply charged argon ions subjected to 2.5 PW/cm 2 laser pulses centered at 800 nm, [21] and with 1.45 µm driving pulses the cut-off energy can even go up to 5.2 keV [22] from krypton atoms. Even if only moderately strong laser pulses, whose peak intensity are not strong enough to produce a significant amount of ions, are available, the bandwidth of NIR-driven IAPs from neutral atoms is still appreciable.…”
mentioning
confidence: 99%
“…As coherent extreme ultra-violet (XUV) light sources, high-order harmonics (HH) radiated from extreme nonlinear optical process in strong laser fields form the basis of attosecond science. High-order harmonic generation (HHG) enables production of ultra-broadband XUV spectra with highest photon energy of up to thousands of keV, [1,2] the generation of single attosecond pulses with pulse durations down to tens of attoseconds, [3][4][5][6] and the investigation of electron and nuclear ultrafast dynamics in matter on timescales ranging from femtoseconds to attoseconds. [7][8][9][10][11][12][13][14][15] Although the strong-field approximation (SFA), in which the liberated electron interacts with strong laser fields, the role of Coulomb potential (CP) needs to be examined for near-threshold harmonics with near-zero electron kinetic energy.…”
mentioning
confidence: 99%